Case report: Association between PTEN-gene variant and an aggressive case of multiple dAVFs - Jong-A-Liem, Glaucia Suzanna; Sarti, Talita Helena Martins; dos Santos, Mariusi Glasenapp; Giacon, Luciano Marcus Tirotti; Wuo-Silva, Raphael; Baeta, Alex Machado; de Campos Filho, José Maria; Chaddad-Neto, Feres (Frontiers in Neurology, 2024)
Introduction Mutations of the phosphatase and tensin homolog (PTEN) gene have been associated with a spectrum of disorders called PTEN hamartoma tumor syndrome, which predisposes the individual to develop various types of tumors and vascular anomalies. Its phenotypic spectrum includes Cowden syndrome (CS), Bannayan–Riley–Ruvalcaba syndrome (BRRS), Proteus syndrome, autism spectrum disorders (ASD), some sporadic cancers, Lhermitte–Duclos disease (LDD), and various types of associated vascular anomalies. Clinical presentation A previously healthy 27-year-old woman was experiencing visual scintillating scotomas and mild chronic headaches for the past 2 years. The initial computed tomographic (CT) and magnetic resonance imaging (MRI) scans did not reveal any abnormalities, but the possibility of pseudotumor cerebri was considered. Furthermore, a cerebral angiogram showed a posterior fossa dural arteriovenous fistula (dAVF), which was initially treated through embolization. However, in spite of proper treatment, this patient experienced multiple recurrent dAVFs in different locations, requiring multiple embolizations and surgeries. Despite exhibiting altered cerebral perfusion and hemodynamics, the patient did not display any significant symptoms until she experienced a sudden stroke resulting from deep venous thrombosis, which was not associated with any medical procedures or medication use. A comprehensive analysis was performed due to the aggressive nature of the dAVFs. Surprisingly, exome sequencing of a blood sample revealed a PTEN gene variant in chromosome 10, indicative of Cowden syndrome. However, no tumors or other vascular lesions were detected in other systems that would constitute Cowden syndrome. Conclusion The rapid formation of multiple and complex dAVFs, coupled with not meeting the criteria for any other PTEN-related syndrome, unequivocally leads to the presentation of a novel phenotype of the PTEN germline variant.